2018
DOI: 10.1108/tqm-02-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Can continuous improvement lead to satisfied customers? Evidence from the services industry

Abstract: Purpose To achieve higher customer satisfaction (CS), companies implement continuous improvement (CI) programs, regardless of the growing evidence of their failure to achieve declared goals. The purpose of this paper is twofold: first, to identify whether companies are able to improve CS through the application of CI; and, second, to identify what organizational practices are able to facilitate the impact of CI on CS. Design/methodology/approach To test the developed assumptions, the study uses the structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 106 publications
(140 reference statements)
2
20
0
Order By: Relevance
“…Value co-creation is an essential element that could help pharmacists improve satisfaction and loyalty precisely with the cooperation of their customers (Andrew et al, 2016;Koval et al, 2018;Wiedmann et al, 2010) P52…”
Section: Mistrust To Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…Value co-creation is an essential element that could help pharmacists improve satisfaction and loyalty precisely with the cooperation of their customers (Andrew et al, 2016;Koval et al, 2018;Wiedmann et al, 2010) P52…”
Section: Mistrust To Cooperationmentioning
confidence: 99%
“…The pharmacists reported having changed their opinions about customer satisfaction and loyalty (Koval et al , 2018). According to 67 percent of the participants, when the mobile apps were introduced, they believed that consumers would change their attitude only slightly.…”
Section: Data Analysis and Findingsmentioning
confidence: 99%
“…TQM is a proven CI approach for organizations to achieve benefits related to elimination of defects and rework, enhanced cost efficiency and employee productivity, reduced operational costs and improved customer satisfaction (Sinha et al , 2016; Valmohammadi, 2011; Khan, 2003; Shenawy et al , 2006). In an empirical study using data of 304 service companies operating in four European nations, Koval et al (2018) noted a direct positive impact of CI on customer satisfaction. The authors found that rewards system and management commitment are the crucial dimensions for enhancing customer satisfaction through CI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…CI approaches has been among the central themes of interest for both academics and practitioners in the field of quality management (Koval et al , 2018; Salah et al , 2010). Many scholars have empirically validated the structural relationship between TQM, one of the established CI methods, and organizational benefits in terms of efficient internal processes, better product/service quality and higher operational performance (Jayad et al , 2019; Sinha et al , 2016; Valmohammadi, 2011).…”
Section: Conclusion Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation